(3TQM TCf GdUdGI heYGdegGs - (3eMeO Hf Ydj Hf GdMSf Hf HTQ, CHh YHO Gddg, GdMcje GdJQePj , J (B320 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfc SCdJfi Yf TCf GdUdGI ef Hjf GdCYeGd , hYf UhQJgG ef Hjf GdCaYGd aC(B/(3G TCf GdUdGI ef Hjf GdCYeGd aEf Gddg JHGQc hJYGdi Ndb gPG GdBOei aGNJGQg Ydi GdHQjI s
(3BNQgG (B:s
(3hGdWGYI hgj GdYUeI , hGdLeGYI hgj GdCdaI , Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B117 - (3U(B171s
(3Ydi GdeLehYI JedcGJ CbOegG SfI (B1198s
(3Ydi GdfSNI ebGHdIs
(3hai UOQgG Jedc HGSe YHO GdQMef Hf CejQ GdeDefjf TQa GdOjf Hf TeS GdOjf CejQ GdeDefjfs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs